Women migration livelihoods and the "fallacy" of the "migrants as a burden to state coffers" : the case of Ghanaian women in the hair care industry in the city of Pretoria - Thebe, Vusilizwe (University of Pretoria, 2018)
Dissertation (MSocSci)--University of Pretoria, 2017.